Partial Blockade of Nitric Oxide Synthase Blunts the Exercise-induced Increase of von Willebrand Factor Antigen and of Factor VIII in Man - Jilma, Bernd; Dirnberger, Eva; Eichler, Hans-Georg; Matulla, Bettina; Schmetterer, Leopold; Kapiotis, Stylianos; Speiser, Wolfgang; Wagner, Oswald F (Thrombosis and Haemostasis, 1997)
Background: Until now the effects of β-adrenergic agonists have largely been ascribed to their ability to induce intracellular formation of cyclic adenosine monophosphate. Recently evidence has been accumulating that at least some β1 and β2-adrenoceptor effects may be mediated by nitric oxide (NO). Based on these studies, we hypothesized that the β-adrenoceptor mediated increase of von Willebrand factor and factor VIII-activity (FVIII:C) in plasma during exercise, is caused by an NO-dependent mechanism. Methods: Thirteen young healthy subjects finished an exhaustive bicycle exercise protocol while they were infused placebo or the NO-synthase inhibitor N-monomethyl-L-arginine (L-NMMA) on two separate days in a randomized, double blind cross-over design. Findings: During exercise systemic haemo-dynamic changes were parallel in both treatment periods, but L-NMMA caused a partial inhibition of NO-synthase as evidenced by a 30% decrease in exhaled NO. The workload capacities were not different during L-NMMA or placebo infusion. However, under placebo treatment exercise increased vWF-Ag by a maximum of 61% (CI: 43-84; p = 0.002) and FVIII:C by 44% (CI: 31-59; p = 0.001), which was significantly attenuated when subjects were treated with L-NMMA (p <0.05): under L-NMMA treatment vWF-Ag increased by only 25% (CI: 5-51; p = 0.001) and FVIII:C by 12% (CI: 6-39; p = 0.001). Interpretation: Partial blockade of NO-synthase with L-NMMA blunts the exercise-induced increase in vWF-Ag and FVIII:C. Our trial points to a role of endogenous NO-generation in the β2-adrenergic increase in vWF/FVIII. Thus, we propose that physiologic processes which are induced by systemic β2-adrenoceptor stimulation may at least partly be mediated by NO.